Quantitative assessment of surface roughness with chlorine dioxide irrigant on root canal dentin by three-dimensional confocal laser scanning microscopy - Rejitha R Kamalasanan; Swapna V Devarasanahalli; M A Ranjini; Mohd Sibghatullah Khatib; Suby Khan; Roopa R Nadig (Wolters Kluwer Medknow Publications, 2018)
Aim: (1) To evaluate the active chlorine concentrations of 3% sodium hypochlorite (NaOCl), 5% chlorine dioxide (ClO2) and 13.8% ClO2using iodometric titration. (2) To evaluate the effects of different concentrations of ClO2 (5% and 13.8%) with or without 17% ethylene diamine tetraacetic acid (EDTA), on the surface roughness of radicular dentin using three-dimensional-confocal laser scanning microscopy (CLSM). Materials and Methods: Fifty extracted human permanent single rooted mandibular premolars were decoronated, longitudinal split into halves and randomly divided into five groups based on the different irrigation regime: Group 1: 3% NaOCl + 17% EDTA, Group 2: 5% ClO2 +17% EDTA, Group 3: 5% ClO2,Group 4: 13.8% ClO2,and Group 5: Saline. The specimens were observed under CLSM to measure the surface roughness. Iodometric titration of the test irrigants were done to evaluate the concentration of active chlorine. Data were statistically analyzed using one-way analysis of variance and Bonferroni test. Results: Mean surface roughness values to root canal dentin were as follows: 13.8% ClO2 >3% NaOCl + 17% EDTA >5% ClO2 + 17% EDTA >5% ClO2> Saline. The active chlorine concentration was highest for 13.8% ClO2and chlorine loss % was highest for 5% ClO2. Conclusion: According to the present study, 5% ClO2produced root canal dentin roughness with minimal erosiveness, which is advantageous. Hence, it can be considered to be an alternate endodontic irrigant. Nearly 13.8% ClO2should be reevaluated as an irrigating solution, because of its significiant dentin roughness and thus it can promote microleakage.